Polimerna nanovlakna za dostavo učinkovin in regeneracijo tkiv pri zdravljenju raka - Potrč, Tanja (Farmacevtski vestnik, 2022)
Nanotechnology offers new possibilities for more ef- ficient and patient-friendly cancer treatment. Polymer nanofibers are in the focus of research in this area. They enable delivery of various types of anticancer drugs, as well as supportive cancer treatment and tissue regeneration after surgery. Nanofibers for oral use are particularly promising, since the oral mucosa is an easily accessible and patient-friendly site for the application of nanofiber-based delivery systems. The polymer nanofibers for local cancer treatment, e.g. oral cavity cancer, or systemic treatment of side effects associated with classical chemotherapy can be produced by electrospinning. Application of na- nofibers with embedded cells represents an inno- vative approach showing great potential in both the cancer treatment and tissue regeneration. Polymer nanofibers are thus expected to enable more efficient treatment of certain cancers and to improve quality of life of cancer patients.
Keywords: dostava učinkovin; drug delivery; nanofibers; nanovlakna; regeneracija tkiv; tissue regeneration